1997
DOI: 10.1021/la962078s
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of Emulsifiers from Polystyrene Latexes Studied by Various Surface Techniques:  A Comparison between XPS, ISS, and Static SIMS

Abstract: The results obtained with three surface spectroscopic methods (XPS, ISS, and static SIMS with quadrupole or time-of-flight analyzers) available for the characterization of the particle surface of polystyrene latexes have been compared. The main point was to quantify the desorption of the surfactants used in the emulsion polymerization (Aerosol MA and sodium dodecylbenzenesulfonate) by the study of both unpurified and purified latexes. A comparison was made between these results and those obtained on a latex pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“…The S 2p 3/2 binding energy of the goethite/parabutlerite nanocomposites is 168.5 eV. This value was agree well with the ones of sulfate (SO 4 2− ) or more exactly (O SO 3 − ) [23].…”
Section: Structures Of the Goethite/parabutlerite Nanocompositessupporting
confidence: 78%
See 1 more Smart Citation
“…The S 2p 3/2 binding energy of the goethite/parabutlerite nanocomposites is 168.5 eV. This value was agree well with the ones of sulfate (SO 4 2− ) or more exactly (O SO 3 − ) [23].…”
Section: Structures Of the Goethite/parabutlerite Nanocompositessupporting
confidence: 78%
“…Fig. 3b shows the S 2p spectrum, which can be perfectly fitted with the S 2p doublet (S2p 3/2 and S2p 1/2 ) by imposing the surface area ratio S2p 3/2 /S 2p 1/2 = 2 [22,23]. The S 2p 3/2 binding energy of the goethite/parabutlerite nanocomposites is 168.5 eV.…”
Section: Structures Of the Goethite/parabutlerite Nanocompositesmentioning
confidence: 90%
“…This suggests that sulfur in the sulfonated PVKs exits in a form similar to sulfonate (SO 3 ). However, as this binding energy is also close to that of sulfate groups in polymers (∼189 eV), it is difficult from the XPS data alone to conclude whether sulfur exists in sulfonate or sulfate form and determine whether sulfur is attached to carbazole units or the backbone of the PVK polymer.
2 XPS S 2p spectrum of sulfonated PVK (PVK-60).
…”
Section: Resultsmentioning
confidence: 99%
“…This fact facilitates total desorption by the use of adsorbent with a high affinity for surfactant, i.e., ion exchange resins. In this way, a recent work (6) showed that after extensive purification by mixed-bed ion exchange resins, the strong acid emulsifier (Aerosol MA) can be completely desorbed. However, the main objective of this paper goes in another direction.…”
Section: Introductionmentioning
confidence: 99%